Strategi Penelusuran dan Pelestarian Naskah Kuno oleh Perpustakaan dan Arsip Deli Serdang - Reni Anjani Sumarno; Retno Sayekti (Universitas Hamzanwadi, 2025)
This study aims to explore the search and preservation strategies of ancient manuscripts implemented by the Deli Serdang Library and Archives. The method used is descriptive qualitative, which allows for in-depth analysis of the preservation process through historical data collection and interviews with related parties. The results of the study indicate that the library applies a non-interventionist approach by keeping the manuscripts in the hands of their owners to respect property rights and cultural sensitivity. In addition, active collaboration with local communities and traditional leaders is key to success in building community trust and participation. This strategy not only maintains the physical preservation of the manuscripts but also strengthens the cultural and social values ​​inherent in the heritage. In conclusion, an approach that prioritizes respect for the community and participatory involvement is an important foundation for the sustainable preservation of ancient manuscripts in Deli Serdang.